Emergence of Oseltamivir-Resistant H7N9 Influenza Viruses in Immunosuppressed Cynomolgus Macaques. (21st June 2017) - Kiso, Maki; Iwatsuki-Horimoto, Kiyoko; Yamayoshi, Seiya; Uraki, Ryuta; Ito, Mutsumi; Nakajima, Noriko; Yamada, Shinya; Imai, Masaki; Kawakami, Eiryo; Tomita, Yuriko; Fukuyama, Satoshi; Itoh, Yasushi; et al.
Summary: Immunosuppressed cynomolgus macaques were infected with an A(H7N9) influenza virus and treated with the neuraminidase inhibitor oseltamivir. Oseltamivir treatment reduced viral titers, but even at high doses failed to block viral replication sufficiently to suppress the emergence of resistant variants. Abstract: Antiviral compounds (eg, the neuraminidase inhibitor oseltamivir) are invaluable for the treatment of individuals infected with influenza A viruses of the H7N9 subtype (A[H7N9]), which have infected and killed hundreds of persons. However, oseltamivir treatment often leads to the emergence of resistant viruses in immunocompromised individuals. To better understand the emergence and properties of oseltamivir-resistant A(H7N9) viruses in immunosuppressed individuals, we infected immunosuppressed cynomolgus macaques with an A(H7N9) virus and treated them with oseltamivir. Disease severity and mortality were higher in immunosuppressed than in immunocompetent animals. Oseltamivir treatment at 2 different doses reduced A(H7N9) viral titers in infected animals, but even high-dose oseltamivir did not block viral replication sufficiently to suppress the emergence of resistant variants. Some resistant variants were not appreciably attenuated in cultured cells, but an oseltamivir-resistant A(H7N9) virus did not transmit among ferrets. These findings are useful for the control of A(H7N9) virus infections in clinical settings.